A review of genre-specific writing scales in ESL/EFL testing contexts - Nimehchisalem, Vahid; Hamidi, Amir (Taylor & Francis, 2016)
As an important part of language assessment, assessing English as a Second or Foreign Language (ESL/EFL) writing has long been the topic of interest among researchers. Writing scales have been used for quite some time in order to decrease the subjectivity of raters' evaluations. While most of the available scales are generic, there are also genre-specific scales which have been developed to be sensitive to the variations that are caused by different genres in the content, organization and structure of the written works to be evaluated. Having discussed the merits and challenges of using writing scales for evaluation purposes, the current paper presents some possible ways in which the usefulness of writing scales can be improved. The paper reviews a number of genre-specific writing scales and concludes with a discussion on their pedagogical implications.